PENERAPAN MODEL PROJECT BASED LEARNING BERBANTU CANVA UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Asnati; Khoimatun; Wahdan Wilsa, Asrizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the completeness of student learning outcomes in Indonesian language subjects, namely as many as 14 students out of 22 students have not completed. Due to the process of learning activities dominated by the teacher, still using conventional models. One of the efforts made is the renewal of the learning model by using the Project Based Learning model with the help of Canva. This study aims to determine the application of the Project Based Learning model assisted by Canva, to determine the increase in creativity and learning outcomes of grade V students of UPTD SDN 3 Juntinyuat. The research method used is Classroom Action Research (PTK) with three cycles using the design model from Kemmis & MC Taggart which consists of four steps, namely: planning, implementation, observation, reflection. This research was applied to grade V students totaling 22 students. The results of student creativity during the learning process increased in cycle I, cycle II, and cycle III. The percentage of cycle I is 65% of the moderately creative category, the percentage of cycle II is 76% of the creative category, and the percentage of cycle III is 81% of the very creative category. Student learning outcomes obtained during the action implementation process have increased. It can be seen from the results of cycle I, cycle II, and cycle III that students met learning completeness and increased in each cycle from 12 students with a percentage of 55% there was an increase to 16 students with a percentage of 73% then increased to 19 students with a percentage of 86%. This research shows that it has reached the 85% classical success indicator. Based on the results of this study, it shows that the Project Based Learning model assisted by Canva can improve the creativity and learning outcomes of elementary school students.